Testing the Constitutional Legitimacy of the Indonesian Capital City: A Historical and Comparative Analysis with the Putrajaya Model in Malaysia - Andi Nur Atika Azizah; Muhammad Ya'rif Arifin; Farah Syah Reza (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to review the development of the Indonesian Capital City (Ibu Kota Nusantara/IKN) within the framework of constitutional law from a historical and comparative perspective with Putrajaya, Malaysia. Using a normative legal research method with statutory, historical, and comparative approaches, this study analyzes the historical formation of the capital city relocation policy and compares the IKN with Putrajaya. The results indicate that the idea of relocating Indonesia's capital city has existed since the Soekarno era, formally realized through Law Number 3 of 2022 on the National Capital City. The relocation is driven by factors such as overpopulation, land subsidence, environmental degradation, and regional development inequality. A comparative study between IKN and Putrajaya reveals that although both share the goal of administrative efficiency, Putrajaya emphasizes modernization of administrative functions within a compact planned city, while IKN envisions a broader purpose as a green, sustainable, and politically representative capital that symbolizes national culture and identity. IKN is designed with 70% green space, renewable energy use, and a phased development plan through 2045. This study recommends that IKN development be carried out sustainably with increased transparency, public participation, and adoption of best practices from global urban planning.